Quality assurance in melanoma surgery: The evolving experience at a large tertiary referral centre. Issue 7 (July 2015) - Read, R.L.; Pasquali, S.; Haydu, L.; Thompson, J.F.; Stretch, J.R.; Saw, R.P.M.; Quinn, M.J.; Shannon, K.; Spillane, A.J.
Abstract Background The quality of melanoma surgery needs to be assessed by oncological outcome and complication rates. There is no published consensus on complication rates for common melanoma surgeries, namely wide excision (WE), sentinel node biopsy (SNB) and regional lymph node dissection (RLND). Consequently there are no agreed standards by which surgeons can audit their practices. Methods Surgical standards were proposed in 2008 following review of the literature and from expert opinion. Melanoma Institute Australia (MIA) self-reported audit data from 2011 and 2012 were compared with these standards. To quality check the self-reported audit, RLND data were extracted from the MIA database. Results Six surgeons performed a mean of 568 surgeries each quarter; with a mean of 106 major procedures. Following WE with primary closure or flap repair, wound infection or dehiscence occurred in <1% of cases. When skin grafting was required non-take of >20% of the grafted area was observed in 5.9% of cases. Following SNB wound infection and significant seroma occurred in 1.8% of cases. RLND node counts were below the 90% standard in 4 of 409 procedures. In comparison, data extraction identified 405 RLNDs, with node counts below the 90% standard in eight procedures. Two of these patients had previously undergone surgery removing nodes from the field and two had gross coalescing disease with extensive extra-nodal spread. Conclusion The quality standards proposed in 2008 have been validated long-term by high volume caseloads. The data presented provide standards by which melanoma surgeons can audit their surgical performance.